English USER SATISFACTION ANALYSIS OF WEBSITE-BASED GRADUATION INFORMATION SYSTEM USING THE PIECES FRAMEWORK METHOD - Danang Purnomo; Meinawati; Wijaya, Masesa Angga (Jurnal Teknologika, 2023)
The world of education today is very dependent on technological advances. The use of these technologies can be utilized as a medium of information. Especially in education at the high school level, the use of technology is necessary to facilitate students. One of the high schools that has used technological advances, especially in information media, is the State Vocational High School (SMKN) 1 Cibatu. The Graduation Information System is an information medium that is currently used by SMKN 1 Cibatu which is already online-based so that information media can be accessed anytime anywhere. However, at this time the developer or school wants to know whether the use of the Graduation Information System is correct or has not been used by its users, an analysis is needed with the aim that later it can be used as a reference for system developers or the school itself in improving/developing information media. so that the media information is made in accordance with the expectations desired by the user. This study uses the PIECES framework analysis method, which is an approach to determine user satisfaction so that maintenance or sustainable development can be carried out later. The output in this study is the result of an analysis of user satisfaction which will later be used as a reference by the developer or the school to develop an even better system.